Stimulation of multiple leader formation in some genotypes of Acacia mangium and Acacia auriculiformis with 6-Benzylaminopurine (BAP) - Eldoma, Ahmed Mohamed Adam; Muniandi, Sures Kumar; Ab Shukor, Nor Aini (Scientific Research Publishing, 2015)
Acacia mangium Willd. and Acacia auriculiformis A. Cunn. ex. Benth. are two of the fast-growing tropical acacias which have received priority for genetic assessment and improvement. They were therefore proposed for timber production in a short rotation in Malaysia but were impeded by the multiple leaders (ML) formation which limited their value as sawn timber. This work attempts to investigate the causes of ML formation in four genotypes of A. mangium and A. auriculiformis as related to apical dominance, nutrition and plant growth hormones and their correlations. The effects of 6-benzylaminopurine and decapitation on ML formation of these genotypes were also investigated. 6-benzylaminopurine (BAP) as a foliar spray and also decapitation did not stimulate ML formation. However, they significantly increased the number of branches and reduced all other growth traits including height. However, basal diameter was not affected by decapitation. The effects of BAP increased consistently with increasing level of application. BAP at 1500 mg·L-1 resulted in mortality of A. mangium provenances while A. auriculiformis provenances survived and grew normally. Some of the BAP treated plants of both species developed juvenile pinnate leaves. Decapitation of the apical bud resulted in the activation of the lateral bud immediately below the point of decapitation.